Supportive Therapy For Reducing Anxiety In Certified Nurse Students Who Are Confirmed Covid 19 Who Are Undergoing Home Quarantine - Andi Nur Aina Sudirman; Firmawati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Covid 19 is a respiratory disease with a high transmission rate and can lead to death. The high number of cases day by day makes patients exposed to Covid-19, both those treated in hospitals and those who are home quarantine felt physical pain, also show somatic symptoms with high anxiety, so it can affect mental health. One of the efforts to overcome anxiety is with supportive therapy. The purpose of this study is to find out supportive therapy for reducing anxiety in certified nurse students who are confirmed Covid 19 who are undergoing home quarantine at the Muhammadiyah University of Gorontalo. This research is a quantitative research with pre-test and post-test designs without control group. The population in this study were certified nurse students who were confirmed Covid 19. The sampling technique used non-probability sampling with the quota sampling technique. The number of sample used was 18 people. Data analysis using paired t test. The results of the study after the intervention showed that there was no anxiety as much as 33.3% and mild anxiety 66.7%. The difference in the average level of anxiety before and after supportive therapy was obtained p value of 0.0001. To reduce the level of anxiety providing psychological support will increase calm. Supportive therapy is also needed to support recovery and prevent further worsening of confirmed Covid-19 patients.